2015
DOI: 10.1177/2158244015574938
|View full text |Cite
|
Sign up to set email alerts
|

Consistency Between Beliefs and Behavior Regarding Use of Substances in Recovery

Abstract: This paper addresses the assumption that pathways to recovery from substance abuse and dependence, and the language used to define one’s relationship to substances, translate to actual beliefs and behaviors in terms of substance use. We draw on social representation theory, and use data from a large web-based study (n=9,341) whose goal was to understand how individuals in recovery define what recovery means to them. We often hear people say that they are “in recovery,” and present findings now provide empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…The proposed definition can be open to interpretation, reflective of the idea that recovery approaches must be individualized to accommodate context, culture, personal beliefs, and severity of substance use. Those with more severe substance use may require abstinence or sobriety, while that may not be realistic or necessary for others (Kaskutas & Ritter 2015;White 2007;Witkiewitz et al 2020). The differences in individuals and the subsequent need for individualization is also reflected in Gonzales et al (2012) who show how youth do not subscribe to substance dependence chronicity models and perceive recovery as a lifestyle change that often does not include abstinence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed definition can be open to interpretation, reflective of the idea that recovery approaches must be individualized to accommodate context, culture, personal beliefs, and severity of substance use. Those with more severe substance use may require abstinence or sobriety, while that may not be realistic or necessary for others (Kaskutas & Ritter 2015;White 2007;Witkiewitz et al 2020). The differences in individuals and the subsequent need for individualization is also reflected in Gonzales et al (2012) who show how youth do not subscribe to substance dependence chronicity models and perceive recovery as a lifestyle change that often does not include abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholics Anonymous, founded in the 1930s on the back of the temperance movement, has long been a proponent of abstinence and 12-step recovery programmes (Witkiewitz et al 2020). Kaskutas and Ritter (2015) showed that exposure to 12-step recovery programmes made participants more likely to identify abstinence as recovery or belonging in recovery definitions. Witbrodt et al (2015) showed that people who are believe in the 12-step recovery programmes are more likely to align themselves with a definition of recovery as abstinence and spirituality, while people who did not follow a 12-step programme were more likely to not endorse abstinence or spiritual elements of recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People appear to recover from SUDs via multiple pathways that may include detoxification, residential intensive treatment, residential supported recovery community reintegration facilities, outpatient services, and mutual-aid groups (Covington, 2002; Green, 2006; Kelly et al, 2017; Sun, 2008). Pathways to recovery may be abstinence-based or moderation-based and may be medication-assisted (Kaskutas & Ritter, 2015; White, 2012). People experience recovery progress inside and outside of treatment contexts.…”
Section: Recovery From Sudmentioning
confidence: 99%
“…In effect, most studies on Twelve-Step programs have been carried out in the context of follow-up on treatment programs, where AA or NA were only one part of a panoply of interventions applied (22,23). One approach to circumventing this limitation has been the solicitation of retrospective observations from persons who have reported prior recovery experiences (24). This approach, however, does not necessarily address persons who have been relieved of substance problems with some Twelve-Step attendance but do not self-identify as "in recovery.…”
Section: Two Culturesmentioning
confidence: 99%